CONTROL OF BIOTOPES MICROFLORA OF ANIMAL ORGANISM – AN IMPORTANT ELEMENT IN RECEIPT OF QUALITY AND SAFE PRODUCTION - Козловська, Г. В.; Скибіцький, В. Г. (Scientific Progress & Innovations, 2013)
In order to find ways to prevent microbial contamination of animal products, the antagonistic effect of known and newly selectioned by probiotic characteristic of strains of lacto-and bifidobacteria on the strains of exciter of intestinal yersiniosis of humans and animals – Yersinia enterosolitica was studied. It was found that antagonistic activity against the latter and other tested test-cultures is characteristic as for some of the known strains of lacto- and bifidobacteria used in the process of obtaining of animal products, and for the newly isolated and selectioned by probiotic characteristic strains.